Finding Religious Moderation on the Indonesian Endorsed Social Studies Textbooks: Critical Discourse Analysis - Solihah, Ni'matus; Abid, Nuskhan (IJTIMAIYA: Journal of Social Science and Teaching, 2022)
Religious moderation manifests an attitude that is not excessive, neutral, and in a middle position. Religious moderation is crucial in a multi-ethnic, multi-cultural, and multi-religious society like Indonesia. This study aims to reveal how indicators of religious moderation are displayed in compulsory social science textbooks in Indonesia—using critical discourse analysis to analyze visual and verbal texts in textbooks. The results show that indicators of religious moderation such as national commitment, tolerance, non-violence, and accommodating to local culture have been included in social science textbooks, although in an unequal proportion. This textual study suggests that other researchers conduct textbook studies using different methods. So, various perspectives will be obtained that can be used as material for future textbook development policies.